Seasonal and daily variations in primary and secondary metabolism of three maquis shrubs unveil different adaptive responses to Mediterranean climate. Issue 1 (5th November 2019) - Gori, Antonella; Tattini, Massimiliano; Centritto, Mauro; Ferrini, Francesco; Marino, Giovanni; Mori, Jacopo; Guidi, Lucia; Brunetti, Cecilia
Abstract: Maquis species play a central role in the maintenance of coastal ecosystems thanks to anatomical, physiological and biochemical features evolved to cope with severe stress conditions. Because the seasonal and daily dynamics of physiological and biochemical traits of maquis species are not fully addressed, we performed a field study on three coexisting Mediterranean shrubs ( Pistacia lentiscus L. and Phillyrea latifolia L., evergreen schlerophylls, and Cistus incanus L., semi-deciduous) aiming at detecting the main adaptive differences, on a seasonal and daily basis, in primary and secondary metabolism along with the principal climatic determinants. These species differed in their physiological and biochemical responses especially on a seasonal level. In P. latifolia, a great investment in antioxidant phenylpropanoids contributed to maintain high photosynthetic rates throughout the whole growing season. In C. incanus, high carotenoid content associated with chlorophyll (Chl) regulation alleviated oxidative damage during the hot and dry summers and help recover photosynthesis in autumn. In P. lentiscus, high abscisic acid levels allowed a strict control of stomata, while fine Chl a /Chl b regulation concurred to avoid photoinhibition in summer. Temperature resulted the most important climatic factor controlling the physiological and biochemical status of these coexisting shrubs and, thus, in determining plant performances in this Mediterranean coastal habitat.